Technostress in Higher Education: A Systematic Literature Review on Psychological Impacts and Academic Outcomes - Dhuha Safria; Viki Sulistia; Refany Novia Siboro (Journal Social Society, 2026)
The rapid integration of digital technologies in higher education has significantly increased the prevalence of technostress among students and academic staff, making it a critical issue within the field of human resource management (HRM). As universities increasingly function as knowledge-based organizations, the management of human capital in digitally intensive environments has become essential. This study aims to systematically review the existing literature on technostress in higher education by examining research trends, geographical distribution, and its theoretical and practical implications. This study employed a Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Secondary data were collected from the Scopus database through a structured keyword search related to technostress and higher education. Journal articles were selected using predefined inclusion and exclusion criteria, resulting in a final sample of 105 Scopus-indexed open-access articles published in English. Data were analyzed using bibliometric analysis to identify publication patterns and thematic analysis to synthesize major research themes and knowledge gaps. The findings indicate that research on technostress in higher education has grown substantially, particularly following the COVID-19 pandemic, reflecting its increasing importance in digitally mediated academic environments. Bibliometric analysis reveals that research is globally distributed but concentrated in several countries, institutions, and journals, while thematic analysis shows that existing studies predominantly focus on the negative psychological consequences of technostress, including stress, fatigue, burnout, and reduced academic performance in digital learning environments. Furthermore, technostress is primarily conceptualized as a technological demand, whereas contextual resources and supportive organizational factors remain underexplored. This study concludes that technostress has become a strategically important research area in higher education and highlights the need for future studies to adopt more balanced, resource-oriented perspectives to support sustainable human resource management and digital transformation in universities.